2019
DOI: 10.1155/2019/2327064
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Simultaneous Determination of Hydroquinone and Catechol in Water Using an Anodized Glassy Carbon Electrode with Polymerized 2-(Phenylazo) Chromotropic Acid

Abstract: Hydroquinone (HQ) and catechol (CT) are considered as environmental pollutants with high toxicity. We have developed a simple electrochemical sensor using an anodized glassy carbon electrode modified with a stable 2-(phenylazo) chromotropic acid- (CH-) conducting polymer (PCH/AGCE). The PCH/AGCE sensor showed good electrocatalytic activity and reversibility towards the redox of HQ and CT in phosphate buffer solution (PBS, pH 7.0). The cyclic voltammetry (CV) in mixed solution of HQ and CT showed that the oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…e binding mechanism of HQ and R is discussed on the basis of surface properties of CAK-S and modeling results. In general, the surfaces of activated carbons are made of acid functions like carboxyl, hydroxyl, quinones, carbonyl, and lactone groups, as well as basic functions like pyrones and chromenes [4,50,51]. For the case of CAK-S, the FTIR and the Boehm titration results, supplemented by EDX/SEM [28], have shown that it has the chemical functions mentioned above.…”
Section: Mechanism Involving Hydrogen Bonding and π-π And N-πmentioning
confidence: 99%
See 2 more Smart Citations
“…e binding mechanism of HQ and R is discussed on the basis of surface properties of CAK-S and modeling results. In general, the surfaces of activated carbons are made of acid functions like carboxyl, hydroxyl, quinones, carbonyl, and lactone groups, as well as basic functions like pyrones and chromenes [4,50,51]. For the case of CAK-S, the FTIR and the Boehm titration results, supplemented by EDX/SEM [28], have shown that it has the chemical functions mentioned above.…”
Section: Mechanism Involving Hydrogen Bonding and π-π And N-πmentioning
confidence: 99%
“…ey mainly come from discharges from textile, petrochemical, petroleum refinery, rubber, dye, plastic, pharmaceutical, and cosmetic industries [2,3]. Several phenolic derivatives such as hydroquinone (HQ) and resorcinol (R) have been recognized as being dangerous pollutants due to their potential toxicity [4]. Wastewater laden with HQ and R is harmful to the environment in general and to the aquatic environment in particular [4,5] because these compounds dissolve and can easily infiltrate the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the redox peaks become prominent on increasing the pH of the solution. At low pH hydroxyl groups of catechol are protonated which decreases its adsorption at the electrode surface due to which decrease in the current is observed 56 .
Figure 7 Effect of variable pH (4.0–9.0) solutions of ( a ) 500 µM catechol ( b ) 500 µM hydroquinone (0.1 M PBS) at CNCs/Zn-TPP/GCE electrode.
…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these defects, numerous efforts have been made to investigate new electrode materials capable of detecting HQ, CC, and RS simultaneously, which include glassy carbon electrode (GCE) modified with allura red polymeric film, multiwalled carbon nanotubes (MWCNTs), MWCNTs/poly­(1,5-diaminonaphthalene) composite film, MWCNTs/ionic liquid (IL) gel, Au nanoparticles (NPs) loaded on poly-3-amino-5-mercapto-1,2,4-triazole-MWCNTs film, AuNPs/sulfonated grapheme, poly amidosulfonic acid/MWCNTs, reduced graphene oxide/magnetite NPs/AuNPs composite, graphene–chitosan composite film, poly­(1,5-diaminonaphthalene), aspartic acid, tyrosinase immobilization with ordered mesoporous C–Au/L-lycine membrane/Au NPs, 3D-flower-like copper sulfide nanoflake-decorated carbon nanofragments, activated phosphate buffer solution (PBS), MWCNT/AgNPs, polyglutamic acid, 2-(phenylazo) chromotropic acid-(CH−) conducting polymer, electrochemically reduced grapheme oxide-poly­(Eriochrome black T)/Au NPs, poly­( p -aminobenzoic acid), tyrosinase/Au NPs encapsulated-dendrimer bonded conducting polymer, self-assembled Ti 3 C 2 /MWCNTs nanocomposites, C/Au nanostructured materials, graphene oxide/polymelamine composite, carbon nanocoils/zinc-tetraphenylporphyrin nanocomposite, nitrogen doped porous carbon nanopolyhedrons-MWCNTs hybrid materials, thionine/graphene oxide, gel of 1-butyl-3-methylimidazolium hexafluorophosphate (BMIHP)/MWCNTs, ammonium carbamate, poly­(malachite green)/MWCNT film, carboxy-functionalized CNTs/chitosan matrix/Au Nps, Pd NPs/poly­(1,5-diaminonaphthalene) matrix; pencil graphite electrode (PGE) modified with CNTs, BIHP, poly­(direct yellow 11), cobalt-phthalocyanine; mesoporous Pd electrode, poly­(crystal violet); flexible screen printed carbon electrode; graphene sheets embedded carbon films; poly­(adenine)/graphene paste electrode; carbon ionic liquid electrode modified with graphene, Au NPs/graphene; gold electrode modified with gold atomic cluster-poly­(3,4-ethylenedioxidethiophene) nanocomposite, etc. However, it remains challenging to investigate novel electrode materials for simultaneous detection of DHBIs with a wide linear range and higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%